Maternal sleep practices: possible risk factor for late stillbirth. (7th June 2011) - Stacey, T; Thomspon, J; Mitchell, E; McCowan, L
Abstract : Introduction: In high income countries, stillbirth occurs in approximately one percent of pregnancies and rates have been static in recent decades. Modifiable risk factors need to be identified so that strategies can be implemented to reduce this tragic pregnancy complication. Aim: To identify modifiable risk factors for late (greater or equal to 28 weeks' gestation) stillbirth, specifically we hypothesised that maternal sleep practices would be associated with third trimester stillbirth. Method: A case control study was conducted in Auckland, New Zealand July 2006–June 2009. Eligible participants were women who had a singleton late stillbirth without congenital abnormality. Two controls were randomly selected at the same gestation as each case. Multivariable logistic regression adjusted for known confounding factors. Results: 155 (72%) cases and 310 (72%) controls consented. Women with a late stillbirth were more likely to be overweight or obese, parity >3, Pacific ethnicity, live in the lowest decile area and smoke, on univariate analysis (p<0.05). After adjusting for BMI and demographic factors, maternal sleep position the night before the stillbirth/interview (not left side vs left side, adjusted OR=2.0 95% CI 1.2 to 3.3) was found to be an independent risk factor for late stillbirth, with a PAR of 37%. Conclusion: This is the first study to report maternal sleep position as a risk factor for stillbirth. Further research is required to confirm these findings. If confirmed, encouraging women to sleep on their left side in late pregnancy has the potential to reduce late stillbirth.